Frequency of Arterial Stiffness in Insulin Resistance and Type 2 Diabetes Mellitus Patients in Tertiary Hospital. (University Heart Journal, 2025)
Background: Arterial stiffness can predict unfavorable cardiovascular events in patients with various illnesses. It is linked to the presence and progression of diabetes complications such as CVD, retinopathy, neuropathy, and nephropathy. Method: This cross sectional study aims to investigate the frequency of arterial stiffness in patients with Type 2 DM. This study was done in Department of Biochemistry and Molecular Biology, BSMMU from March 2022 to February 2023. Results: 95 type 2 diabetes mellitus patients aged 40 to 70 yrs from Endocrinology and Metabolism OPD of BSMMU were included here. Subjects were divided into two groups on the basis of arterial stiffness which was assessed by measuring brachial ankle pulse wave velocity (bapwv). Group 1 had bapwv ≥1815cm/s was considered as type 2 DM patients with arterial stiffness and Group 2 with bapwv